Croup syndrome and primary infection with mycobacterium tuberculosis in children - L. I. Mozzhukhina; O. G. Chelnokova; T. A. Kogut; A. L. Salova (Медицинский совет, 2019)
Acute respiratory viral infections (ARVI) occupy an important place in infectious pathology of children’s age. One of the frequent and severe manifestations of ARVI, accompanied by respiratory disorders, is stenosing laryngotracheitis (croup syndrome). Primary stenosing laryngotracheitis develops, as a rule, in children of the second-third year of life, rarely-older than 5 years. In 30–50% of patients, croup syndrome recur, often accompanied by signs of bronchial obstruction. The reasons for the formation of the relapses studied enough: discusses the role of concomitant allergic diseases, immune dysfunction, autonomic reactivity, etc. At the same time, the importance of such background conditions as the infection with Mycobacterium tuberculosis, the presence of local forms of tuberculosis (TB) in children in the development of croup syndrome and its recurrence in the literature is not reflected. In the course of our study, it was found that children with primary and recurrent croup are often infected with Mycobacterium tuberculosis at the age of 5 years, which allows them to be classified as at risk of tuberculosis infection; recurrent croup is significantly more often implemented in the early period of primary infection with Mycobacterium tuberculosis and the development of local forms of TB. Chemoprophylaxis and TB therapy can reduce the risk of developing recurrent croup syndrome in 82% of patients. Thus, one of the possible factors in the etiopathogenesis of the syndrome of croup can be a TB infection.